Neurogenomics from the Catholic tradition. A succinct anthropological perspective taking into account nowadays developments in the fields of genetics and neuroscience - Carrara, Alberto (Studia Bioethica, 2017)
There was a time in which genes played a central role in scientific and popular scenarios. Now it is the time of another principal character: the human brain. More than 10 years ago, prominent neuroscientist Steven Rose portrayed with these words the raise of the so call ‘golden neurocentric age’